Analisis Kinerja Keuangan Bank Syariah Indonesia (BSI) Sebelum dan Setelah Merger - Shafira Arista Putri; Dini Dewindaru; Eha Nugraha (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2023)
Purpose: This study aims to determine the effect of mergers on BSI's financial performance. Research methodology: The method used in this research is descriptive comparative, namely research that describes a certain situation within a predetermined period of time. The data used in this study comes from the financial statements of the three Islamic banks before the merger (2019) and BSI after the merger (2021). Results: The results of this study show that of the nine ratios studied, six ratios have increased, namely the quick ratio, debt to equity ratio, times interest earned, return on assets, return on equity, and net profit margin, while the other four have decreased, namely the current ratio, cash ratio , and debt ratios. Limitations: The observation period is limited to a year before and a year after the merger. Contribution: As for suggestions for BSI, it is necessary to pay attention to important and dominant aspects that can improve the quality of company assets and financing. Novelty: The difference between this study and previous studies is that the ratios used in this study are Current Ratio (CR), Quick Ratio (QR), Cash Ratio, Debt Ratio (DR), Debt to equity ratio (DER), Times interest earned (TIE), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) as a comparison to see the financial performance before and after the merger from BSI.